Back RIver Sewage Disposal Plant - Waldeck (1913)
Handwritten in black: Black river sewage disposal plant. Preston Administration. Handwritten in white: 8110. Aug-18-13. Disposal Works. By Waldeck. Sticker on recto reading: 46